CDC5 Inhibits the Hyperphosphorylation of the Checkpoint Kinase Rad53, Leading to Checkpoint Adaptation - Vidanes, Genevieve M. (Public Library of Science, 2010)
The Saccharomyces cerevisiae polo-like kinase Cdc5 promotes adaptation to the DNA damage checkpoint, in addition to its numerous roles in mitotic progression. The process of adaptation occurs when cells are presented with persistent or irreparable DNA damage and escape the cell-cycle arrest imposed by the DNA damage checkpoint. However, the precise mechanism of adaptation remains unknown. We report here that CDC5 is dose-dependent for adaptation and that its overexpression promotes faster adaptation, indicating that high levels of Cdc5 modulate the ability of the checkpoint to inhibit the downstream cell-cycle machinery. To pinpoint the step in the checkpoint pathway at which Cdc5 acts, we overexpressed CDC5 from the GAL1 promoter in damaged cells and examined key steps in checkpoint activation individually. Cdc5 overproduction appeared to have little effect on the early steps leading to Rad53 activation. The checkpoint sensors, Ddc1 (a member of the 9-1-1 complex) and Ddc2 (a member of the Ddc2/Mec1 complex), properly localized to damage sites. Mec1 appeared to be active, since the Rad9 adaptor retained its Mec1 phosphorylation. Moreover, the damage-induced interaction between phosphorylated Rad9 and Rad53 remained intact. In contrast, Rad53 hyperphosphorylation was significantly reduced, consistent with the observation that cell-cycle arrest is lost during adaptation. Thus, we conclude Cdc5 acts to attenuate the DNA damage checkpoint through loss of Rad53 hyperphosphorylation to allow cells to adapt to DNA damage. Polo-like kinase homologs have been shown to inhibit the ability of Claspin to facilitate the activation of downstream checkpoint kinases, suggesting that this function is conserved in vertebrates.